2016
DOI: 10.1080/01612840.2016.1222039
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Psychoeducation Given to Caregivers of People With a Diagnosis of Schizophrenia

Abstract: The aim of this study was to evaluate the effectiveness of psychoeducation given to caregivers of patients diagnosed with schizophrenia on their perceptions of burden and on clinical course of patients. This was a quasi-experimental study with pre-post tests and a control group and designed as a nonrandomized controlled intervention trial. While the patients in both the intervention and the control group received treatment as usual (TAU), only the caregivers in the study group were offered two sessions of psyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 40 publications
1
16
0
6
Order By: Relevance
“…This result is consistent with soliman et al [25] who found that psycho education was effective both in improving patients, medical condition and improving caregivers perception of illness resulting in reducing the family burden. Also supported with the findings of Bulut et al, [26] as they mentioned that psycho education leading to improve caregivers perception of illness.…”
Section: Discussionsupporting
confidence: 85%
“…This result is consistent with soliman et al [25] who found that psycho education was effective both in improving patients, medical condition and improving caregivers perception of illness resulting in reducing the family burden. Also supported with the findings of Bulut et al, [26] as they mentioned that psycho education leading to improve caregivers perception of illness.…”
Section: Discussionsupporting
confidence: 85%
“…The results also showed that when the caregivers felt they were not able to cope with symptomatic behaviors in caregiving process, they become more critical/hostile (Akbulut, 2009). Moreover, psychoeducation is one of the effective ways to cope with burden (Bulut, Arslantaş, & Ferhan Dereboy, 2016). This study examines families’ position in caregiving process, and this is one of the first studies to approach the caregiving burden of families in a qualitative way.…”
Section: Introductionmentioning
confidence: 99%
“…A pesar de estas limitaciones metodológicas, nuestros resultados coinciden con los encontrados en otros estudios previos que utilizan diseños con mayor validez interna (Bulut, Arslantas y Ferhan Dereboy, 2016;Chien, Chan y Thompson, 2006;Chien y Wong, 2007;Koolaee y Etemadi, 2010;Martin-Carrasco et al, 2016;Navidian et al, 2012) así como con los de varias revisiones sistemáticas y meta-análisis (Chen et al, 2016;Yesufu-Udechuku et al, 2015).…”
Section: Limitaciones Del Estudiounclassified